Assessment and modelling the antibacterial efficacy of vapours of cassia and clove essential oils against pathogens causing foodborne illness. (October 2021) - Basak, Suradeep; Singh, Jahnavi Kumari; Morri, Shravneshwary; Shetty, Prathapkumar Halady
Abstract: The present study deals with assessment of antibacterial activity of essential oil vapours (EOV) of cassia ( Cinnamomum cassia ) and clove ( Syzygium aromaticum ) using dose-response equation, and modelling the inactivation pattern of Escherichia coli, Salmonella enterica serovar Typhi and Yersinia enterocolitica under the influence of EOVs using three-parameter Weibull model. The fitted inhibition (%) data to dose-response equation estimated 0.98 and 3.63 μL/cm 3 as concentration of cassia and clove EOV that could inhibit the growth of E. coli up to 90%, whereas estimated IC90 for cassia and clove EOV against S. enterica ser. Typhi was 0.52 and 1.33 μL/cm 3, respectively. However, Y. enterocolitica exhibited more sensitivity under the influence of cassia and clove EOVs with IC90 of 0.2 and 0.79 μL/cm 3, respectively. The inactivation model estimated 3.1 and 4.4 h required by cassia and clove EOV for 1-log10 reduction of E. coli, respectively. Similarly, 1-log CFU reduction of Y. enterocolitica under the influence of cassia and clove EOV were estimated to be 3.6 and 5.1 h, respectively, and S. enterica ser. Typhi showed highest δ -value for both the selected EOVs. Susceptibility of the bacteria strains to the EOVs can be attributed to the antibacterial efficacy of the chemical components present. Highlights: Biochemical composition of EO of cassia and clove was analysed using GC-HRMS. Antibacterial efficacy of EOV was assessed using dose-response curve equation. Modified Weibull model described bacterial inactivation under the influence of EOV.